2023
DOI: 10.3390/microorganisms11020333
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Aeromonas veronii in Sheep with Fatal Infection in China: A Case Report

Abstract: According to the findings of a sheep breeding farm in Shaanxi, China, 2.53% (15/594) of sheep exhibited respiratory (clinical) symptoms such as dyspnoea, nasal discharge, wet cough, fever, and progressive emaciation. Although multi-drug treatment strategies (including ampicillin, tylosin, florfenicol, and ceftiofur) have been attempted to improve clinical outcomes, they have only been met with limited success, with a mortality rate of 40%. Ultimately, Aeromonas veronii (A. veronii) was identified as the causat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the current investigation discovered that A. veronii is susceptible to antibiotics of aminoglycosides group; gentamycin (10 µg), fluroquinolones group; endrofloxacin (10 µg) and quinolones group; nalidixic acid (30 µg), there is a possibility that these antibiotics could control the A. veronii infections in fish farms. Hassan et al (2017) also found A. veronii to be sensitive to nalidixic acid, however Miao et al (2023) discovered resistance to gentamycin and enrofloxacin. Antimicrobial resistance has become a serious issue in aquaculture due to abuse of antibiotics not only as disease control agents but also as growth boosters.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the current investigation discovered that A. veronii is susceptible to antibiotics of aminoglycosides group; gentamycin (10 µg), fluroquinolones group; endrofloxacin (10 µg) and quinolones group; nalidixic acid (30 µg), there is a possibility that these antibiotics could control the A. veronii infections in fish farms. Hassan et al (2017) also found A. veronii to be sensitive to nalidixic acid, however Miao et al (2023) discovered resistance to gentamycin and enrofloxacin. Antimicrobial resistance has become a serious issue in aquaculture due to abuse of antibiotics not only as disease control agents but also as growth boosters.…”
Section: Resultsmentioning
confidence: 99%
“…The LD 50 of A. veronii varies for different aquatic animals [ 28 ]. The LD 50 for longsnout catfish and largemouth bass was 3.47 × 10 4 CFU/g [ 29 ] and 3.72 × 10 4 CFU/g [ 30 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant colonies were picked for purification culture. Identification was performed as previously described [14]. The genomic DNA of isolates were extracted by a genomic DNA purification kit (DAKEWE, Shenzhen, China) according to manufacturer recommendations.…”
Section: Microbial Isolation and Identificationmentioning
confidence: 99%
“…Hu sheep, a renowned sheep breed in China, stands out for its remarkable characteristics of early maturation and exceptional productivity [13]. There have been a growing number of reported cases of sheep pneumonia in China in recent years [9,14]. Moreover, numerous studies have endeavored to characterize the variability of lung microbiotas in healthy sheep [15,16].…”
Section: Introductionmentioning
confidence: 99%